Debt Bias and Other Distortions : Crisis-Related Issues in Tax Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Tax distortions are likely to have encouraged excessive leveraging and other financial market problems evident in the crisis. These effects have been little explored, but are potentially macro-relevant. Taxation can result, for example, in a net subsidy to borrowing of hundreds of basis points, raising debt-equity ratios and vulnerabilities from capital inflows. This paper reviews key channels by which tax distortions can significantly affect financial markets, drawing implications for tax design once the crisis has passed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet